Throughput analysis of buffered CSMA/CD based single channel Fast Ethernet optical LAN - Shamima, Kabir; Sabira, Khatun; M. K., Abdullah; M. A., Mahdi; S. B., Ahmad Anas (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/